Analisis Faktor Penyebab Keterlambatan Pelaksanaan Proyek Konstruksi pada CV. X Menggunakan Metode FTA - Putra, Dwi Meilana; Triana, Masca Indra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Delays that are not handled immediately can affect the quality of a company's performance. This research was conducted on a construction project undertaken by CV. X. Where 4 construction projects undertaken by CV. X as of January 2024 experienced delays in completion. For this reason, it is necessary to analyze the factors that cause delays in the project by using the FTA (Fault Tree Analysis) method which aims to find fault trees from various errors that will result in the occurrence of unwanted events. Data collection is done by survey using a questionnaire. The results of the questionnaire were then analyzed using the FTA Method and then determining the combination of these factors with a minimum cut set. Based on the results of the analysis using the FTA Method, there are 6 aspects that are factors causing delays, namely aspects of labor; material / equipment aspects; project implementation management aspects; contract aspects; aspects of work documents; aspects of natural conditions and force majors. With the largest probability value, namely the contract aspect of 0.21; project implementation management aspect of 0.18; material / equipment aspect of 0.15; aspects of natural conditions and force majors of 0.12; aspects of work documents of 0.09; aspects of labor of 0.08.